Environmentalism and NGO accountability - Yekini, Kemi C.; Yekini, Liafisu Sina; Ohalehi, Paschal (Bingley, U.K. : Emerald Publishing Limited, 2020)
It is increasingly being recognised across society that the preservation of our natural environment should shape political, economic and social policies. This book delves into the partnership of non-governmental organisations (NGOs), Environmental NGOs (ENGOs), their communities, and their governmental counterparts in responding to this need. Providing extended research on environmentalism and the NGOs' roles in promoting environmental accountability, the chapters present a comprehensive overview of the interaction between the two themes both regionally and internationally. Topics include the accountability of Environmental NGOs (ENGOs), impact of NGOs on environmental sustainability, NGOs and sustainable development goals, NGOs and social reporting quality, and the role of NGOs in urban and rural environmental governance. The authors present these insights within the context of developing economies, continental and global perspectives, as well as the transformational angle. This book provides readers with a truly comprehensive snapshot of the environmental accountability of NGOs.
Chapter 1: Review of Environmentalism and NGO Accountability; Kemi C. Yekini, Liafisu Sina -- Chapter 2: Achieving Sustainability through Environmental Social Governance (ESG) Reporting: Overcoming the Challenges; C.O. Mgbame, A. Aderin, Paschal Ohalehi, and A.M. Chijoke-Mgbame -- Chapter 3: Developing Local Government's Socio-Environmental Accountability: Insights from Indonesian Socio-Environmental NGOs Annual Reports; Habib Muhammad Shahib, Eko Ganis Sukoharsono, M. Achsin, and Yeney Widya Prihatiningtias -- Chapter 4: Environmental Accountability, NGOs and Extended Producer Responsibility in Nigeria: The Views of Corporate Responsibility Officers and Accountants; I.I. Okwuosa -- Chapter 5: NGOs' Engagements and Ghana's Environmental Accounting Disclosure Quality; H. Maama, J.O. Akande and M. Doorasamy -- Chapter 6: Impact of the Oversight Role of NGOs on the Environmental Reporting and Social Responsibility of Listed Manufacturing Companies in Nigeria; A.A. Adeyemi, O.T. Bakare, A.J. Akindele, and O. Soyode -- Chapter 7: Reviewing the Business of Non-Governmental Organizations in African Transformation; N.M. Ojo and O.P. Mafimisebi -- Chapter 8: NGO Accountability on Environmentalism: A Literature Review of Relevant Issues and Themes; Liafisu Sina Yekini and Kemi C. Yekini.
Includes index.
Includes bibliographical references.
Print version record.
Keywords: Non-governmental organizations -- Environmental aspects; Environmentalism; Business & Economics, Nonprofit Organizations & Charities -- General; Non-governmental organizations (NGOs).